Smart Medicine Dropbox - Elias, Muhammad Danial; Ahmad, Shukri; Abdul Rahman, Hadi; Mohd Haris, Nazir (Multidisciplinary Applied Research and Innovation, 2022)
The medicine giving system at pharmacy counters in most hospitals in Malaysia, especially government hospitals is still at an unsatisfactory level where there are many weaknesses in the service system to patients especially in process of giving medicine, where that problem is faced by most patients who seeking treatment at hospital. Following that, a new innovation needs to be introduced to address the problems identified as weaknesses in the existing medicine administration system such as the process of giving medicine or medicine reception to patients takes a very long time and becomes worse when the number of patients increases because hospital or more specific government hospital is main attraction of Malaysians causing the situation at the pharmacy counter is often crowded because the process of taking medicine. Furthermore, in the post -epidemic era all patients are strongly encouraged not to be in crowded areas, due to that, a new innovation called "SMART MEDICINE DROPBOX" (SMD) was built to help the old system in overcoming the problems identified, especially the problem of the process of administering medicine to patients. Having several (SMD) at the pharmacy counter can make the medicine administration process more faster at one time. The method used to develop this system is by using Arduino software and GSM SIM900A as it communication platform between two different user. It has also been tested several times and got quite good results.